2018
DOI: 10.3389/fonc.2018.00497
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Hsp70—A Novel Target for the Isolation of Circulating Tumor Cells After Epithelial-to-Mesenchymal Transition

Abstract: The presence of circulating tumor cells (CTCs) in the peripheral blood is a pre-requisite for progression, invasion, and metastatic spread of cancer. Consequently, the enumeration and molecular characterization of CTCs from the peripheral blood of patients with solid tumors before, during and after treatment serves as a valuable tool for categorizing disease, evaluating prognosis and for predicting and monitoring therapeutic responsiveness. Many of the techniques for isolating CTCs are based on the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 40 publications
0
26
0
1
Order By: Relevance
“…Interestingly, in contrast to EpCAM, the EMT does not downregulate HSP70 expression as higher membrane-bound HSP70 (mHSP70) expression has been found on metastatic tumors compared to its primary counterparts [131,[206][207][208][209]. In this regard, Stangl and colleagues used HSP70-TKD peptide to develop monoclonal antibody directed against mHSP70 for specific targeting mHSP70-positive tumors by NK cells and efficient isolation of CTCs [206,210]. Taken together, on the one hand, high surface expression of HSP70 is found in metastatic tumors and mHSP70 may serve as a biomarker for assessing the metastatic spread.…”
Section: Hsp70 In Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in contrast to EpCAM, the EMT does not downregulate HSP70 expression as higher membrane-bound HSP70 (mHSP70) expression has been found on metastatic tumors compared to its primary counterparts [131,[206][207][208][209]. In this regard, Stangl and colleagues used HSP70-TKD peptide to develop monoclonal antibody directed against mHSP70 for specific targeting mHSP70-positive tumors by NK cells and efficient isolation of CTCs [206,210]. Taken together, on the one hand, high surface expression of HSP70 is found in metastatic tumors and mHSP70 may serve as a biomarker for assessing the metastatic spread.…”
Section: Hsp70 In Metastasismentioning
confidence: 99%
“…Clinically, circulating tumor cells (CTCs) that underwent EMT serve as a prognostic marker of a metastatic spread and can be isolated from patient's blood using epithelial cell adhesion molecule (EpCAM) as a cell surface marker [206]. Interestingly, in contrast to EpCAM, the EMT does not downregulate HSP70 expression as higher membrane-bound HSP70 (mHSP70) expression has been found on metastatic tumors compared to its primary counterparts [131,[206][207][208][209]. In this regard, Stangl and colleagues used HSP70-TKD peptide to develop monoclonal antibody directed against mHSP70 for specific targeting mHSP70-positive tumors by NK cells and efficient isolation of CTCs [206,210].…”
Section: Hsp70 In Metastasismentioning
confidence: 99%
“…Later, plasma membrane-bound HSP70 was proposed to be used as a specific easily detectable marker of CSC-like circulating tumor cells that have undergone EMT and consequently lost the epithelial cell surface markers EpCAM and CD326 [126]. As well as HSP90, HSP70 was found in exosomes secreted by prostate cancer cells undergoing hypoxic stress [20].…”
Section: Extracellular and Cell Surface-bound Hsp70mentioning
confidence: 99%
“…Many reports revealed that HspA1A is found in association with sphingomyelin/cholesterol rich lipid domains (lipid rafts) [ 5 , 18 , 19 , 20 , 21 ]. Therefore, several investigators aim to target the cell surface/PM-localized HspA1A as a novel anti-cancer treatment [ 5 , 22 , 23 , 24 ]. It is also fairly well established that HspA1A’s PM localization depends on its interaction with intracellular PS and other lipids, including globotriaoslyceramide, which is primarily found in lipid rafts [ 6 , 7 , 25 ].…”
Section: Discussionmentioning
confidence: 99%